Indolent primary effusion lymphoma-like lymphoma in the pericardium: A case report and review of the literature. Issue 5 (May 2019) - Yamaoka, Osamu; Matsui, Toshiki; Nishiyama, Keizo; Miyamoto, Akashi; Shiota, Hiromi; Kawahara, Chiho; Shikano, Mayumi; Nagao, Masatoshi; Minamiguchi, Hitoshi; Takemura, Shizuki
Abstract: We report a rare case of a 75-year-old man with a history of mild-to-moderate pericardial effusion that was detected on echocardiography performed in October 2011 when the patient was 69 years old. Follow-up echocardiography was performed every 6 months thereafter, showing that the pericardial effusion gradually subsided. However, in April 2017 he started experiencing several episodes of dyspnea, which prompted him to visit our hospital's outpatient department on June 22, 2017. Echocardiography revealed a large amount of pericardial effusion; thus, he was immediately hospitalized. After undergoing pericardiocentesis and drainage, 1740-ml of bloody pericardial fluid was collected. Serum antibody tests for human immunodeficiency virus, hepatitis C virus, and human herpes virus 8 were negative, whereas that for Epstein–Barr virus (EBV) was positive, indicating a prior infection. Cytopathological examination, immunocytochemical staining, lymphocyte surface marker analysis, and cytogenetic assessment were performed. EBV-encoded small ribonucleic acid in situ hybridization was negative. He was diagnosed with primary effusion lymphoma (PEL)-like lymphoma (LL) and was treated with 8 doses of rituximab 375 mg/m 2 over a 2-month period. He has remained in complete response for the past 12 months. Our case shows the possibility of long-term existence of indolent PEL-LL in patients with mild-to-moderate pericardial effusion. <Learning objective: Primary effusion lymphoma (PEL)-like lymphoma (LL) is a rare disease with a poorly understood pathophysiology. Some patients are able to achieve a complete response after drainage of the effusion without chemotherapy. We experienced a case of PEL-LL, which was only diagnosed after 6 years of continually observing the pericardial effusion. Cardiologists should consider PEL-LL as a differential diagnosis in patients with unexplained pericardial effusion.>